Imaging of Appendicitis in Adults - Karul, M.; Berliner, C.; Keller, S.; Tsui, T. Y.; Yamamura, J. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Three imaging modalities are available for the diagnosis of acute appendicitis: ultrasound (US), computed tomography (CT), and magnetic resonance imaging (MRI). Transabdominal ultrasound should be the first-line imaging test. Abdominal CT is superior to US and is required immediately in patients with atypical clinical presentation of appendicitis and suspected perforation. However, low-dose unenhanced CT is equal to standard-dose CT with intravenous contrast agents in the detection of five signs of acute appendicitis (thickened appendiceal wall more than 2 mm, cross-sectional diameter greater than 6 mm, periappendicitis, abscess, and appendicolith). MRI is necessary in pregnant women and young adults. This review illustrates the principles of state-of-the-art imaging techniques and their clinical relevance.Key Points:• US is the basic diagnostic method in case of suspected appendicitis.• CT is necessary in patients with atypical presentation of appendicitis.• MRI should be the first-line imaging test in pregnant women.Citation Format:• Karul M, Berliner C, Keller S et al. Imaging of Appendicitis in Adults. Fortschr Röntgenstr 2014; 186: 551 – 558
Keywords: abdomen; CT; MR imaging; ultrasound; appendicitis